Village websites as promotional media for tourist destinations in Sukajadi Village, Tamansari, Bogor - Iwan Setyawan; Aris Fatoni; Filda Angellia; Nuraini Purwandari; Kampono Imam Yulianto (Universitas Muhammadiyah Magelang, 2022)
Sukajadi Village is a village in Bogor's Tamansari District, located on the slopes of Mount Salak. Beautiful nature, as well as natural tourist attractions such as waterfalls and historical sites, are tourist destinations with the potential to boost the village's revenue and the local economy. However, the general public has only received limited information about one tourist attraction, such as Curug Nangka, despite the presence of other equally beautiful destinations. The primary objective of this community service program is to create a village website to help promote tourist destinations in Sukajadi Village. The Systems Development Life Cycle (SDLC) Model is used to develop the website. The results of this program show that the citizens of Sukajadi Village can promote tourist destinations as well as other villages' potential, such as culinary tourism.